PARADIGMA KRITIS DAN AKSIOLOGI DALAM PENGEMBANGAN MANAJEMEN KEINGINAN DI LEMBAGA BISNIS - Elly Rahayu; Wan Mariatul Kifti; Rahma Muti'ah; Siti Mujiatun (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This riset conceptually explores the analysis of power structures in the management of desires inside modern business organizations via the lens of critical paradigms and how axiological principles such as justice, sustainability, and autonomy might steer business practices towards enhanced ethicality and introspection. The critical paradigm method aims to "uncover" the concealed mechanisms underlying the formation and regulation of desires (for example, via marketing and self-responsibilization) to expose the ideological hegemony that sustains injustice. The action approach, on the other hand, stresses the importance of making moral ideals a part of company plans and practices. The synthesis of recent literature indicates that in the absence of normative values, business practices are susceptible to manipulation, exploitation, and the abuse of power, including market power. Companies that continuously adhere to ethical norms, such as justice, social responsibility, and openness, tend to exhibit greater competitiveness and longevity. This article asserts that establishing critical paradigms in desire management enhances accountability for socio-ecological consequences, while axiological values function as a normative guide to ensure that businesses do not solely "manage desires" for profit but also honor consumer autonomy, maintain distributive justice, and safeguard environmental sustainability. Practical implications necessitate the establishment of corporate policies that prioritize public welfare, in accordance with OECD guidelines on Responsible Business Conduct, coupled with the enhancement of consumer critical literacy to foster collective awareness that enables structural protections against market dominance